Characteristics, Contents and Origins of Persian Weblogs Pertaining to Women's Issues - Abkooh, Elaheh Taheri (2010)
Weblogs prepare a new form of online community where users come together to share opinions and analysis about prevalent events and other issues. In fact weblogs are interesting form of large social network. Blogging provides a way for women and men to become active creators and publishers of knowledge writing about what is important to them. Considering the importance of weblogs about women issues, this study aimed to evaluate blogging about women issues in two woman days (14th June and 8th March) in which Iranian people celebrate them. The study period is two weeks; a week in June and a week in March. The objective of the study was specifically to determine 1) To identify the characteristics of weblogs in women issues network, 2) To identify the main content of the women’s issues that discuss on Persian blogs, 3) To determine the differences in content between blogs originating from Iran and blogs originating from outside of Iran, 4) To determine the differences in content between weblogs in the months of March and June in 2009, 5) To identify the hub in the network of women issues weblogs. The content analysis was employed as the method for data collection and assessment. The unit of analysis consisted of all posts and paragraphs that discussed about women’s issues. The population of the study consisted of 415 weblogs from the Blogfa hosting. Then 150 of active, Persian language and text-based weblogs are selected for this study. These constituted the majority of active blog covering women’s issues in two women-related days in Iran. Data were analyzed by SPSS and descriptive statistics such as frequencies and percentages were used. Most coverage of women issues by Persian weblogs was political issues. This study revealed the political subjects like freedom, sexuality separation in universities and suppression of women by government were most important issues among Persian bloggers in Iran. Based on this study blogs with different origin attended to different women issues. The findings of this study showed that political events were most important women issues among blogs originating from Iran and women’s right and women abuse were important women issues among blogs originating from outside of Iran. In addition, this study determined the differences in contents between weblogs in the months of March and June. The findings revealed that women’s right, Job issues, gender specific projects in Iran and women’s share in economic were the most noteworthy content in March 2009. On the other hand, political event, abuse of women, gender restriction, family issues, religion and health were the most important issues in June 2009. The findings also showed that the hub of women issues blogs was a blog from outside of Iran that mostly focuses on political issues of women. The study found that blogs characteristics were substantial however some characteristics were used more than the others. The study found that place of origin, politically –based blogs, gender were special factors in women issues network. The findings showed that most of bloggers in this study were women with good response to their readers that wrote about women issues individually.